Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I think I may be missing something here,

$$f(x,y)=\left\{ \frac {xy(x^{2}-y^{2})}{x^{2}+y^{2}}\right.\quad(x,y)\neq (0,0)$$

Let $X(s,t)= s\cos(\alpha)+t\sin(\alpha)$ and $Y(s,t)=-s\sin(\alpha)+t\cos(\alpha)$, where $\alpha$ is a constant, and Let $F(s,t)=f(X(s,t), Y(s,t))$. Show that

$$ \left.\frac{\partial^2 F}{\partial s^2}\frac{\partial^2 F}{\partial t^2} - \left( \frac{\partial^2 F}{\partial s\partial t}\right)^2 = \left(\frac{\partial^2 f}{\partial x^2}\frac{\partial^2 f}{\partial y^2} - \left(\frac{\partial^2 f}{\partial x\partial y}\right)^2\right)\right| _{x=X(s,t),y=Y(s,t)} $$

I decided to try and subsitute My $X(s,t)$ and $Y(s,t)$ into $f(x,y)$, however im just wondering if thre is an alternative approach as it gives a lot of terms, many thanks in advance.

I have gone away and had a think about the answer and still not sure where to put my best foot forward with it so:

$ \frac{\partial^2 F}{\partial s^2}=cos^{2}\alpha\frac{\partial^2 F}{\partial ^2X}$ $\Rightarrow$ $ \frac{\partial^2 F}{\partial t^2}=sin^{2}\alpha\frac{\partial^2 F}{\partial ^2X}$

Now using the fact that $\frac{\partial^2 F}{\partial ^2X}$ is equal to $\frac{\partial^2 f}{\partial ^2X} | _{x=X(s,t)}$ to calculate our $\frac{\partial^2 F}{\partial ^2X}$.

Now $\frac{\partial^2 f}{\partial ^2X}$= $ \frac{-4x^{4}y-20x^{2} y^{3}+8x 3y^{3}-4x y^{5}+4x^{5} y+10x^{3} y^{3}+6x y^{5}}{(x^{2}+y^{2})^{3}}$ hence do I make the subsitution here, seems to be far to many terms and havent even got to the RHS, many thanks in advance.

share|cite|improve this question
up vote 0 down vote accepted

Let $f:\ (x,y)\mapsto f(x,y)$ be an arbitrary function and put $$g(u,v):=f(u\cos\alpha + v\sin\alpha, -u\sin\alpha+v \cos\alpha)\ .$$ Using the abbreviations $$c:=\cos\alpha, \quad s:=\sin\alpha,\quad \partial_x:={\partial\over\partial x}, \quad\ldots$$ we have (note that $c$ and $s$ are constants) $$\partial_u=c\partial_x-s\partial_y, \quad \partial_v =s\partial_x+ c\partial_y\ .$$ It follows that $$\eqalign{g_{uu}&\cdot g_{vv}-\bigl(g_{uv}\bigr)^2 \cr &=(c\partial_x-s\partial_y)^2 f\cdot (s\partial_x+ c\partial_y)^2 f -\bigl((c\partial_x-s\partial_y)(s\partial_x+ c\partial_y)f\bigr)^2 \cr &=(c^2 f_{xx}-2cs f_{xy}+s^2 f_{yy})(s^2 f_{xx}+2cs f_{xy}+c^2 f_{yy}) -\bigl(cs f_{xx}+(c^2-s^2) f_{xy}-cs f_{yy}\bigr)^2 \cr &=\ldots =f_{xx}\, f_{yy} -\bigl(f_{xy})^2\ . \cr}$$ This shows that the stated identity is true for any function $f$ and not only for the $f$ considered in the original question.

There should be a way to prove this identity "from a higher standpoint", i.e., without going through this tedious calculation.

share|cite|improve this answer

I might be wrong but actually the only helpful thing i see is that $X^2 + Y^2=s^2+t^2$,so in your $f(X,Y)$ you'll get:

$$ \begin{align} f(X,Y)& =\frac{XY(X^2-Y^2)}{X^2+Y^2} \\ \\ \\ & =\frac{((t^2-s^2)\sin(a)\cos(a)+st(\cos^2(a)-\sin^2(a))(t^2-s^2)(\sin^2(a)-\cos^2(a))}{t^2+s^2} \end{align} $$

Alternatively you could use the chain rule where $\frac{\partial F}{\partial s}=\frac{\partial F}{\partial X}\frac{\partial X}{\partial s}=\cos(a)\frac{\partial F}{\partial X}$ where $\frac{\partial X}{\partial s}=\cos(a)=ct$. The partial derivative $\frac{\partial F}{\partial X}$ is actually the same as $(\frac{\partial f}{\partial x})_{x=X}$, something you will compute anyway. So you will have $\frac{\partial^2 F}{\partial s^2}=\cos(a)\frac{\partial\frac{\partial F}{\partial X}}{\partial s}=\cos(a)\frac{\partial\frac{\partial F}{\partial X}}{\partial X}\frac{\partial X}{\partial s}=\cos^2(a)\frac{\partial\frac{\partial F}{\partial X}}{\partial X}=\cos^2(a)\frac{\partial^2F}{\partial X^2}$. Likewise you can compute the other partial derivatives for F.

share|cite|improve this answer
little unsure about my edit. – user24930 Mar 1 '12 at 11:19

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.